1990
DOI: 10.1192/bjp.156.4.479
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Consequences of the Enniskillen Bombing

Abstract: Eleven people were killed and 60 injured in the Enniskillen bombing of November 1987. Survivors were psychologically appraised six months and one year later. At six months 50% had developed post-traumatic stress disorder (PTSD). This group comprised more females than males. However, all victims had high scores on the GHQ. We found no correlation between psychological injury (as measured by the GHQ) and physical injury (as measured by the ISS), calling into question previous assertions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
4

Year Published

1993
1993
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(52 citation statements)
references
References 11 publications
1
47
0
4
Order By: Relevance
“…Women reported long-term effects and depression (Cairns & Mallett, 2003;Curran et al, 1990;Hayes & Campbell, 2000;McWhirter, 2002;O'Reilly & Stevenson, 2003;Potter, 2004), whereas men expressed resentment and anger (Dillenburger et al, 2007b): (My grown up children) say I have to forget him and they think I should be over it after all these years [10 years]. But I will never forget (1985/86).…”
Section: Individual Factorsmentioning
confidence: 99%
“…Women reported long-term effects and depression (Cairns & Mallett, 2003;Curran et al, 1990;Hayes & Campbell, 2000;McWhirter, 2002;O'Reilly & Stevenson, 2003;Potter, 2004), whereas men expressed resentment and anger (Dillenburger et al, 2007b): (My grown up children) say I have to forget him and they think I should be over it after all these years [10 years]. But I will never forget (1985/86).…”
Section: Individual Factorsmentioning
confidence: 99%
“…Following the bombing in Enniskillen (northern Ireland) in 1987 in which eleven people were killed and 60 injured, all victims had high scores on the GHQ indicating poor mental health when examined at six months and at one year, and 50% of the survivors examined had developed PTSD at six months (3). The significance of this finding to the August seventh l998 bomb blast in Nairobi where casualties were much higher are self evident and demand urgent systems of surveillance of the population.…”
Section: Introductionmentioning
confidence: 65%
“…In that study, 34% of the directly exposed bombing survivors were diagnosed with PTSD in the 6-month postbombing period. Despite the variety of diagnostic methods applied, the other studies of terrorist events identified in table I reported similar rates of PTSD (Curran et al, 1990), identifying the diagnosis in approximately one-fourth to one-half of directly exposed survivors following these major terrorist events. Intentionally perpetrated acts such as terrorism are thought to have more severe mental health consequences on survivors than natural disasters and technological accidents (Baum et al, 1983), presumably related to the heinous intent behind the incident.…”
Section: Posttraumatic Stress Disorder In Populations Directly Exposementioning
confidence: 93%